New Schottky diode based entirely on nickel aluminate spinel/p-silicon using the sol-gel spin coating approach - Gunduz, B.; Al-Ghamdi, Ahmed A.; Hendi, A. A.; Gafer, Zarah H.; El-Gazzar, S.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2013)
A new kind of p-type Schottky diode was successfully fabricated based entirely on Al/NiAl2O4/P-Si/Al spinel using the sol-gel spin coating approach. The estimated values of particle size and surface roughness of the as prepared NiAl2O4 film are found to be 168-362 nm and 27.735 nm, respectively. The electrical properties of the Al/NiAl2O4/P-Si/Al diode were characterized in terms of current-voltage (I-V) and capacitance-voltage (C-V) techniques. The rectification ratio and ideality factor of the Al/NiAl2O4/P-Si/Al diode is decreased by increasing temperature. It was observed that there is a difference between the ideality factor obtained from the forward bias semi-log I-V plot and dV/d(InI) vs. I plot. The electrical parameters at room temperature of the as fabricated Al/NiAl2O4/P-Si/Al diode such as built-in potential, acceptor concentration, barrier height different temperatures and frequencies were determined from the capacitance-voltage measurements. It is found that the values of the acceptor concentration are decreased, while the values of the built-in potential are increased with increasing frequencies of the diode. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Nickel aluminate spinel; Microstrucure; Electrical properties; Schottky diode